Cleaner production strategies in steam methane reforming process for hydrogen production / Thineswary Naidu Genggayanaidu - Thineswary Naidu, Genggayanaidu (2021)
Hydrogen gas is a clean fuel, when consumed in a fuel cell, produces only water. It makes an attractive fuel option for transportation and electricity generation application. As the world moves towards a more sustainable approach, hydrogen gas has a promising future in the role to play as a clean energy. Among the different technologies, steam methane reforming (SMR) is the most vital and economic process, being used in most of the hydrogen manufacturing industries. SMR comes with advantages such as initial low capital investments, greater scalability and sitting flexibility for locations unable to accommodate more traditional larger reactors. Besides that, SMR also has the potential of enhanced safety and security compared to other technology available. However, the drawback is that SMR emits significant carbon dioxide (CO2) emissions as a byproduct of hydrogen production. For 1 kg of hydrogen produced, about 4 kg of CO2 is emitted directly from the process alone, not accounting to the indirect CO2 emission. Therefore, in this work, an overall assessment was conducted for the full life cycle of steam methane reforming process to identify possible greening opportunities using cleaner production (CP) strategy. From this initiative, a checklist and general guideline that can be used to green the current operations has been developed in order to reduce the carbon footprint. Thereafter, a CP audit was carried out in a SMR production site which is located at Melaka. Based on the analysis, carbon footprint can be possibly reduced from 7,430 tons monthly to 4,963 tons monthly for the current hydrogen production monthly with all the CP options iv proposed. This is equivalent to 66.8 % of reduction from the total of 7,430 tons of CO2 emitted without implementing any CP strategies. Based on the CP options, those falls under the category of implementation without cost (immediate actions) are given the highest priority followed by implementation with cost, whereby the Rate of Investment (ROI) is lesser than 5 years and future implementation. The three finest CP options were installing steam traps at the steam drum, changing the current technology to electrolysis and installing Carbon Capture and Storage (CCS) to the existing SMR has tremendous potential to reduce carbon footprint, increases the efficiency of the process and improves the quality of the product.